The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2008
DOI: 10.1575/1912/2346
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization and expression of molluscan detoxification enzymes and transporters involved in dietary allelochemical resistance

Abstract: Understanding how organisms deal with potentially toxic or fitness-reducing allelochemicals is important for understanding patterns of predation and herbivory in the marine environment. The ability of marine consumers to tolerate dietary toxins may involve biochemical resistance mechanisms, which increase the hydrophilicity of compounds and facilitate their active efflux out of sensitive cells and tissues. While several allelochemical-responsive detoxification enzymes have been sequenced and functionally chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2008
2008
2010
2010

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 336 publications
1
4
0
Order By: Relevance
“…Thus, high expression of GST mu isoforms may allow C. gibbosum to tolerate the chemical defenses of its host and subsequently feed longer than would otherwise be possible. Preliminary studies have demonstrated that prostaglandins found in gorgonians significantly inhibit Cyphoma GST activity in vitro [49], consistent with the idea that gorgonian prostaglandins may be substrates for Cyphoma GSTs.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Thus, high expression of GST mu isoforms may allow C. gibbosum to tolerate the chemical defenses of its host and subsequently feed longer than would otherwise be possible. Preliminary studies have demonstrated that prostaglandins found in gorgonians significantly inhibit Cyphoma GST activity in vitro [49], consistent with the idea that gorgonian prostaglandins may be substrates for Cyphoma GSTs.…”
Section: Discussionsupporting
confidence: 66%
“…Rather, the high GST activity may reflect an adaptation that facilitates consumption of allelochemical-rich prey. Additional findings indicate that C. gibbosum GSTs are expressed constitutively at high levels regardless of the gorgonian diet, providing further support for this hypothesis [49]. Whether high GST activity is common among marine species that feed exclusively on chemically defended food is unknown, and may depend upon the specific suite of allelochemicals present in the diet.…”
Section: Discussionmentioning
confidence: 70%
“…HPLC separation of affinity-purified GSTs identified fourteen unique peaks (see Figure S1 ). HPLC peak 1 was previously identified as a theta-class GST, while HPLC peaks 2 thru 14 were identified as mu-class GST subunits [44] . HPLC peaks 4 and 8 represented the majority of expressed GST subunits at 25% and 68%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Cytosolic and affinity-purified GSTs were isolated from Cyphoma digestive gland samples as described in [44] . Briefly, cytosolic GSTs were isolated by homogenizing digestive glands (n = 39) separately in buffer (0.1 M potassium phosphate, 1 mM EDTA, 1 mM DTT, 1.15% potassium chloride, protease inhibitor cocktail (1×); pH 7.5), and differentially centrifuging the homogenates to obtain the cytosolic fraction containing the soluble GST pool.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation